(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Canaliculitis is a rare inflammation of the lacrimal canaliculi with a relapsing course and a poor response to treatment. According to research findings, canaliculitis is revealed in 2.4% of cases among newly-admitted ophthalmic patients. Inflammation of the lacrimal canaliculi can be caused by fusobacteria, nocardia, staphylococci, actinomycetes, aspergilla, candida, herpes simplex virus, and herpes zoster, as well as lacrimal punctum occluders left accidently [1]. Canaliculitis is most commonly of a chronic character and characterized by complication development due to late diagnosis and continuous inadequate treatment. Diagnosis difficulties make up to 72.4 % and contribute to process chronicity. The most reasonable treatment is considered to be canaliculotomy, an ophthalmological surgical procedure when the lacrimal canaliculus is incised, its discharge is removed followed by rinsing with antiseptics and antimicrobial agents [1].